Pathological Crosstalk Between Oxidized LDL and ER Stress in Human Diseases: A Comprehensive Review - Varghese, Divya Saro; Ali, Bassam R. (Frontiers in Cell and Developmental Biology, 2021)
The oxidative modification of the major cholesterol carrying lipoprotein, oxLDL, is a biomarker as well as a pathological factor in Cardiovascular Diseases (CVD), Type 2 Diabetes Mellitus (T2DM), obesity and other metabolic diseases. Perturbed cellular homeostasis due to physiological, pathological and pharmacological factors hinder the proper functioning of the Endoplasmic Reticulum (ER), which is the major hub for protein folding and processing, lipid biosynthesis and calcium storage, thereby leading to ER stress. The cellular response to ER stress is marked by a defensive mechanism called Unfolded Protein Response (UPR), wherein the cell adapts strategies that favor survival. Under conditions of excessive ER stress, when the survival mechanisms fail to restore balance, UPR switches to apoptosis and eliminates the defective cells. ER stress is a major hallmark in metabolic syndromes such as diabetes, Non-Alcoholic Fatty Liver Disease (NAFLD), neurological and cardiovascular diseases. Though the pathological link between oxLDL and ER stress in cardiovascular diseases is well-documented, its involvement in other diseases is still largely unexplored. This review provides a deep insight into the common mechanisms in the pathogenicity of diseases involving oxLDL and ER stress as key players. In addition, the potential therapeutic intervention of the targets implicated in the pathogenic processes are also explored.